The Importance of the Board-President Relationship in Three Community Colleges - Levin, John S. (Canadian Journal of Higher Education, 1991)
Governance and management in institutions of higher education have attracted considerable attention in the North American literature. While much has been published concerning the respective roles of the president and the governing board in managing the affairs of colleges and universities, limited attention has been given to the relationship which exists between the two parties. The purpose of this study is to examine the board-president relationship in the academic institution in order to discern reasons for the importance of the relationship. The investigation uses qualitative-interpretive research methods in an examination of three colleges in the province of British Columbia. Five major conclusions are presented to indicate reasons for the importance of the board-president relationship. First, at the three colleges, the board and the president see themselves as having influence and impact upon the external community. Second, at the three colleges, the board and the president see themselves as having influence and impact upon the internal college community. Third, there is a high level of value compatibility among board members and the president, based on the accounts of the parties. Fourth, board and president together view themselves as the chief authorities of the institution, responsible for the governance and management of the operations of their colleges. And fifth, at the three colleges, board and president together, in their expressed attitudes and actions, mirror perceived characteristics of the larger organization.